Influences of Career Planning, Leadership and Organizational Culture towards Employee Work Effectiveness - Hafni Rizanuddin (Budapest International Research and Critics University, 2020)
This study was conducted at the Regional Civil Service Agency of Majalengka Regency. The purpose of this research is to analyze the influence of career planning, organizational culture and the leadership simultaneously and partially to the effectiveness of employee work. The methods used in this research are descriptive and verification methods. The primary data collection was conducted using census techniques, i.e. the entire population was used as the subject of research. Data sources in this research are primary and secondary data, with data analysis techniques using path analysis. The results showed that career planning conducted by Regional Civil Service Agency of Majalengka Regency is well-perceived; the leadership of the Regional Civil Service Agency of Majalengka Regency is well perceived. That is, the leader of Regional Civil Service Agency of Majalengka Regency has been carrying out his tasks and functions fairly well, especially in order to improve the basic task of Regional Civil Service Agency in providing public services; the organizational culture that makes up the organizational values and norms is well-perceived; Employees at Regional Civil Service Agency of Majalengka Regency are assessed as effective in carrying out their daily work; Career planning is verification a positive and significant influence on the effectiveness of employee work; Leadership proved to have a positive and significant influence on employee work effectiveness; The organizational culture is empirically positive and significant influence on the effectiveness of work; Simultaneously between career planning, leadership and organizational culture affects positively and significantly to the effectiveness of the work.